Morphology and histology of reproductive organ and first screening of wolbachia in the ovary of red palm weevil, Rhynchophorus ferrugineus (coleoptera: dryophthoridae) - Wan Nurul ‘Ain W.M.N.,; Nurul Wahida O.,; Yaakop S.,; Norefrina Shafinaz M.N., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
This study was conducted to assess intracellular bacteria Wolbachia in the ovaries of female Red Palm Weevil (RPW), Rhynchophorus ferrugineus from three populations in Malaysia by means of PCR using wsp- specific primer. The morphology and histology of ovary of RPW were also studied and examined by stereo microscope LEICA EZ4 HD that was equipped with LAS EZ software and light microscope Zeiss Axio Scope with iSolutionLite software respectively. We found that the adult female had two pairs of ovaries, lateral oviduct, common oviduct, bursa copulatrix, spermatheca and vagina. Histological study of the ovariole revealed that it is categorised under polytrophic ovariole. The ovariole is divided into four regions, the terminal filament, the germarium, the vitellarium and the stalk or calyx. Besides, the infection status showed that all three populations were not infected with Wolbachia. Our result suggests that no infection of Wolbachia in RPW reproductive system.